EKSPLORASI PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ARTS, MATHEMATICS) PADA PENDIDIKAN DASAR DAN PENDIDIKAN ANAK USIA DINI - St Adrianti; Mirdayati Aihena; Febri Yuridnir Rahimah; Romi Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The twenty-first-century educational landscape demands holistic competencies, yet the implementation of the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in early childhood and primary education in Indonesia remains fragmented, frequently reduced to isolated activities lacking meaningful interdisciplinary integration. This study systematically explores the conceptual foundations, implementation patterns, pedagogical benefits, and systemic challenges of STEAM across both educational levels. Employing a systematic literature review methodology, 42 peer-reviewed articles, conceptual papers, and policy reports published between 2015 and 2025 were analyzed through thematic synthesis and content analysis. Data were retrieved from Scopus, ERIC, Google Scholar, SINTA, and DOAJ using predefined inclusion criteria. Results indicate that STEAM significantly enhances critical thinking, creativity, collaboration, and socio-emotional resilience when delivered through play-based, inquiry-driven, and project-oriented learning aligned with developmental stages. However, implementation is hindered by teachers’ limited interdisciplinary pedagogical competence, rigid curricular structures, inadequate learning resources, and product-focused assessment paradigms. Effective integration necessitates sustained teacher professional development, flexible curriculum alignment with Indonesia’s Merdeka Curriculum, culturally responsive adaptations, and authentic assessment frameworks. These findings provide evidence-based guidelines for educators, school leaders, and policymakers to optimize STEAM implementation and foster sustainable, child-centered educational transformation.